2018
DOI: 10.17826/cumj.341676
|View full text |Cite
|
Sign up to set email alerts
|

Hekimlerin human papillomavirus enfeksiyonu ve aşısı ile ilgili farkındalıkları ve yaklaşımları

Abstract: ÖzPurpose: To evaluate the awareness of human papillomavirus (HPV) infection and attitude of the vaccination of the medical doctors among HPV vaccination. Material and Methods: A total of 147 medical doctors (98 from the department of Obstetrics and Gynecology and 49 from the department of pediatrics) were enrolled into this study. A survey which measure the knowledge and attitude about HPV infection and vaccination received by the participants. Statistical analyses were performed to evaluate and compare the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
0
0
0
2
Order By: Relevance
“…In the study of Makwe and Anorlu (2011), it was found that the participants did not consider to getting vaccinated with the HPV vaccine as they did not see themselves at risk for the HPV (Makwe and Anorlu, 2011). Additionally, in another study that was conducted with physicians, the physicians stated that they did not want to have HPV vaccine because of the low risk of HPV transmission (Topçu et al, 2018). Additionally, in this study, 37.8% of the participants stated that they wanted to have the HPV vaccine (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of Makwe and Anorlu (2011), it was found that the participants did not consider to getting vaccinated with the HPV vaccine as they did not see themselves at risk for the HPV (Makwe and Anorlu, 2011). Additionally, in another study that was conducted with physicians, the physicians stated that they did not want to have HPV vaccine because of the low risk of HPV transmission (Topçu et al, 2018). Additionally, in this study, 37.8% of the participants stated that they wanted to have the HPV vaccine (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This result shows that nurse academicians have high health beliefs about the HPV vaccine and encourage young people to be vaccinated. Çeşmeci et al (2015) reported that 89.4% of the intern doctors stated that they would be recommending HPV vaccine to their friends and relatives in the appropriate age group (Çeşmeci et al, 2015); Esposito et al (2007) reported that 84.8% of the healthcare professionals stated that they have been recommending HPV vaccine (Esposito et al, 2007); in another study it was reported that 85% of the obstetricians and 78% of the pediatricians-primary care physicians stated that they have been recommending HPV vaccine (Topçu et al, 2018). Realization of health protection and promotion behaviors and Individuals' beliefs are very important in maintaining.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Literatürden farklı olarak çalışmamızda, hekimlerin gerek kendilerine gerekse hastalarına aşı önermeleri konusunda aşının maliyetinin daha az öneme sahip olduğu dikkati çekmiştir. [11][12][13] Ülkemizde yapılan birçok anket çalışmasında, HPV aşısının hekimler tarafından sıklıkla önerildiği görülmekle birlikte, kişinin kendisine aşıyı yaptırma oranının genellikle daha düşük olduğu dikkat çekmektedir. [14][15][16] Bizim çalışmamızda ise, katılımcıların %15.3'ü HPV aşısını yaptırmıştı ve yine %84,7'si çocuğunu da aşılamayı planlıyordu.…”
Section: Discussionunclassified
“…17 Yine ülkemizde yapılan 147 hekim katılımcının değerlendirildiği bir çalışmada ise, aşılanma oranı %2,8'dir. 13 Çalışmamızda, katılımcıların %15,3'ü HPV aşısı yaptırmıştı; bunların %53,3'ünün pediatri uzmanı olduğu, %40'ının ise pediatri asistanı olduğu dikkati çekmiştir. Bu durumun pediatri uzmanlarının HPV aşısı hakkında daha fazla bilgi sahibi olabileceklerine ve aşı uygulama yaşı itibariyle bu grubun aşıyı daha fazla uygulatmasına bağlı olabileceği düşünülmüştür.…”
Section: Discussionunclassified